Identifying the segments and elements of a value proposition for Quensus Ltd. - Arbelaez, Manuel (2016)
This document is the result of a study carried out during a three-month project that aimed to help Quensus, a new start-up that specializes on leak detection and water management, with the identification of the segments to target and elements to include in a value proposition for them. A co-creation framework developed by Helle in 2010 was adapted to the needs of this project and applied to five different segments namely Student Accommodation, SMEs, Local Councils, Water Utilities and Facility Management firms. Interviews with different firms from these segments and data obtained from secondary sources helped on the identification of opportunities and needs around water management and leak detection within these firms. By matching these opportunities against the different resources available at Quensus, the real possibilities for Quensus to work with these segments were narrowed down. Subsequently, after identifying real business cases, efficiency tests, run for the customer and Quensus, and effectiveness tests, run for the customer, helped on the identification of cost optimization and revenue variation opportunities respectively. All this helped on the calculation of joint productivity gains which highlighted the overall potential value available behind each segment. The results show how two segments, FM firms and Local Councils, are more likely to find good value in the solutions provided by Quensus, mainly because of the high impact that leaks currently have in their operations. On the other hand, Student Accommodation, SMEs and Water Utilities are segments which today might find less value in Quensus’ solutions mainly because of the high cost that they would have to pay for the solution versus the economic benefits obtained from it. Along the document, the different elements considered to be of value for the mentioned segments are touched and highlighted in the recommendations and conclusions sections. All these results are based on the information obtained so far, meaning that new opportunities that might come from further interaction with firms from the different segments could imply a variation on them. Nevertheless, with the methodology followed, the insights obtained become a good approach towards the identification of the segments and the elements they value.